Equilibrium, kinetics, thermodynamics and desorption studies of pentachlorophenol onto agricultural waste activated carbon. (2020) - Kavitha, D.
Abstract: Coir-pith derived activated carbon has been shown to be a feasible adsorbent for the extracting pentachlorophenol from aqueous medium. The adsorption was studied by varying the dosage of carbon, contact time, concentration of the adsorbate, temperature and pH. Kinetic studies revealed fast adsorption with equilibrium attained at 60 and 80 min for adsorbate concentrations (10-40 mg/L). The second order model was best described in the experimental kinetics. Analyzed the equilibrium data by applying well known isotherm models. The principle of adsorption has been confirmed by estimation of thermodynamic parameters like standard entropy, enthalpy and free energy.